Dataset: High emission rates and strong temperature response make boreal wetlands a large source of isoprene and terpenes - Lejish Vettikkat; Pasi Miettinen; Angela Buchholz; Pekka Rantala; Hao Yu; Simon Schallhart; Tuukka Petäjä; Roger Seco; Elisa Männistö; Markku Kulmala; Eeva-Stiina Tuittila; Alex B. Guenther; et al. (Zenodo, 2022)
Dataset used in the article "High emission rates and strong temperature response make boreal wetlands a large source of isoprene and terpenes" The tab-delimited file contains direct surface-atmosphere Volatile Organic Compound fluxes, measured by Eddy Covariance with a Vocus- proton transfer reaction mass spectrometer (Vocus-PTR) at a subarctic fenduring 2021. It also contains PAR (Photosynthetic Active Radiation), temperature and fluxquality criteria.